PELATIHAN MICROSOFT POWER POINT DALAM MENINGKATKAN KETERAMPILAN TEKNOLOGI SANTRI DI PESANTREN PAQUSATTA KUTAI TIMUR - Firdaus, Firdaus; Aminah, Aminah; Listia Wati, Nur; Saputra, Reshar; Mayang Sari, Silviana; B, Irwan; Muhammad, Muhammad (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2025)
In today's digital era, mastery of information technology is a skill that must be possessed by the younger generation, including students in the pesantren environment. This service activity aims to improve students' digital literacy through training on the use of Microsoft Power Point as one of the commonly used presentation software in the world of education and work. The training was carried out at the Sangatta Taqwa Qur'an Islamic Boarding School (Paqusatta), East Kutai, using the Participatory Action Research (PAR) method which emphasizes the active participation of participants in every stage of the activity, starting from planning, implementation, to evaluation. The results showed that there was an improvement in the participants' basic skills in using Microsoft PowerPoint, such as composing slides, adding visual elements, and applying animations and transitions. The evaluation carried out through observation and assessment of practical results showed high enthusiasm and increased student competence in composing digital presentations creatively. Obstacles faced include device limitations and variations in participants' initial abilities. Overall, this training succeeded in encouraging the mastery of students' digital skills, while strengthening their ability to convey messages in a modern and communicative manner.